Nurturing the Next Generation / Special Issue on the Neglect of Pre-Degree Psychology - Sutton Jon; The British Psychological Society (2007)
The Teenage Social Brain, Interview - Evolutionary Psychology, What to Expect From Your Psychology Degree, The Social Brain of a Teenager, Today's Fish and Chip Paper and Tomorrow's Career.